Evaluasi Prosedur Dokumen Harga Transfer PT ABJ - Lukman Surjadi; Jonathan Patrick (Jurnal Ekonomi, 2022)
The preparation of this report and internship practice was done in order to get an overview of the working world and know the procedure to make a transfer pricing document for ABJ Company. The internship was held at PT XYZ, for four months starting from January 3rd, 2022 to 28th April,2022. The procedure for ABJ Company’s transfer pricing document was given one week of working time. PT XYZ and ABJ Company must coordinate to prepare all the data needed in making the transfer pricing document. ABJ Company required the company’s transfer pricing document to prove that transactions made by ABJ Company with its affiliates are fair and common. The benefits obtained during the internship period are many, such as developing soft skills such as building good teamwork, establishing good communication with clients, thinking critically and more logically, and being able to manage time better.